Demographic mechanisms of disturbance and plant diversity promoting the establishment of invasive Lupinus polyphyllus. (18th May 2016) - Jauni, Miia; Ramula, Satu
Abstract: Aims: Community characteristics, such as disturbances and interspecific competition that affect the availability of microsites and resources, contribute to the success or failure of the establishment of exotic plant species. In particular, these two community characteristics may have adverse effects on plant emergence and survival, which are particularly important for population establishment and therefore it may be necessary to consider both these vital rates simultaneously when assessing demographic mechanisms. Here, we investigated the impacts of disturbance and interspecific competition on the establishment of a perennial invasive herb, Lupinus polyphyllus Lindl. Methods: Over the course of 2 years, we conducted an experiment in 10 populations of this species in Finland in which we manipulated the levels of soil disturbance. We recorded community characteristics (i.e. the number of vascular plant species, vegetation height, and the proportions of bare ground, litter and moss), and observed the emergence and survival of L. polyphyllus individuals in study plots. Important Findings: A mild disturbance (breaking the soil surface mechanically) slightly increased seedling emergence but did not affect plant survival. Instead, an intense disturbance (vegetation and litter removal) had no effect on seedling emergence, although it significantly increased the proportion of bare ground and, consequently, seedling survival. Survival was not affected by the height of the surrounding vegetation, but both seedling emergence and plant survival increased with an increasing number of plant species in the study plots. These findings demonstrate that single disturbance events may considerably promote the establishment of invasive herbs, although the overall effect and demographic mechanisms behind the increased establishment are likely to vary depending on disturbance type. Moreover, our results suggest that species diversity per se may not be a crucial mechanism for locally preventing the establishment of exotic plants.